Pharmacokinetic Studies of Tobramycin and Gentamicin - Simon, V. K. (1973)
Broth dilution susceptibility tests of 100 isolates of Pseudomonas aeruginosa and 101 isolates of Staphylococcus aureus against tobramycin (formerly nebramycin factor 6) and gentamicin showed that tobramycin was more effective against P. aeruginosa and less effective against S. aureus. The minimal inhibitory concentration of tobramycin against the Pseudomonas sp. isolates that required 5 μg of gentamicin per ml for inhibition ranged from 0.63 to 0.31 μg/ml. Peak concentrations in the blood of 10 healthy adults after intramuscular injection of 80 and 40 mg of tobramycin averaged 3.7 ± 0.62 and 2.4 ± 0.27 μg/ml, and declined to 0.56 ± 0.05 and 0.26 ± 0.02 μg/ml, respectively, after 6 h. The urine recovery averaged 60%. The half-life was 1.6 h. During continuous intravenous infusion of tobramycin and gentamicin (infusion rate 6.6 mg per h), blood levels at steady state were 0.94 ± 0.10 and 1.04 ± 0.06 μg/ml, respectively. For both antibiotics, the calculated distribution volume ranged from 15 to 17 liters. The renal clearance to tobramycin averaged 76% and that of gentamicin averaged 85% of the total clearance, indicating that the drugs are primarily eliminated by the kidneys. The present results suggest that tobramycin may be more successful in the treatment of Pseudomonas infections than gentamicin at the same dosage (80 mg intramuscularly three to four times daily).